From Basic Visual Science to Neurodevelopmental Disorders: The Voyage of Environmental Enrichment-Like Stimulation. (6th May 2019) - Consorti, Alan; Sansevero, Gabriele; Torelli, Claudia; Berardi, Nicoletta; Sale, Alessandro
Abstract : Genes and environmental stimuli cooperate in the regulation of brain development and formation of the adult neuronal architecture. Genetic alterations or exposure to perturbing environmental conditions, therefore, can lead to altered neural processes associated with neurodevelopmental disorders and brain disabilities. In this context, environmental enrichment emerged as a promising and noninvasive experimental treatment for favoring recovery of cognitive and sensory functions in different neurodevelopmental disorders. The aim of this review is to depict, mainly through the much explicative examples of amblyopia, Down syndrome, and Rett syndrome, the increasing interest in the potentialities and applications of enriched environment-like protocols in the field of neurodevelopmental disorders and the understanding of the molecular mechanisms underlying the beneficial effects of these protocols, which might lead to development of pharmacological interventions.